2019
DOI: 10.18632/aging.102492
|View full text |Cite
|
Sign up to set email alerts
|

Molecular subtypes based on DNA methylation predict prognosis in colon adenocarcinoma patients

Abstract: Tumor heterogeneity makes early diagnosis and effective treatment of colon adenocarcinoma difficult. As an important regulator of gene expression, DNA methylation can influence tumor heterogeneity. In this study, we explored the prognostic value of subtypes based on DNA methylation status in 424 colon adenocarcinoma samples from the Cancer Genome Atlas database. Differences in DNA methylation levels were associated with differences in T, N, and M category, age, stage, and prognosis. Seven subgroups were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 29 publications
0
46
0
Order By: Relevance
“…To understand the mechanism of cancer, help guide therapy, and improve prognoses, it is vital to identify accurate subtypes. Several studies reported identifying subtypes based on DNA methylation, including colon adenocarcinoma [ 36 ], cervical cancer [ 37 ], glioblastoma [ 38 ], and bladder cancer [ 39 ]. This study divided BC into three distinct subtypes based on the immune-cell-related methylation profiles ( Figure 1 B–C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the mechanism of cancer, help guide therapy, and improve prognoses, it is vital to identify accurate subtypes. Several studies reported identifying subtypes based on DNA methylation, including colon adenocarcinoma [ 36 ], cervical cancer [ 37 ], glioblastoma [ 38 ], and bladder cancer [ 39 ]. This study divided BC into three distinct subtypes based on the immune-cell-related methylation profiles ( Figure 1 B–C).…”
Section: Discussionmentioning
confidence: 99%
“…(3) Probes on the X and Y chromosomes were excluded from the analysis [ 96 ]. The remaining sites were imputed with the k-nearest neighbors (KNN) imputation procedure [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…With the development of RNA-seq technology, many classical analyses based on gene expression data have been reported for most cancers (6,(38)(39)(40). However, few cluster studies have been performed on PCa to explore the tumor metabolic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…With the progress of high-throughput gene sequencing technology, more and more genes have been put into practical use as speci c therapeutic targets and prognostic markers for malignant tumors (11,12).…”
Section: Introductionmentioning
confidence: 99%